Diversification of ceramic craft for tourism souvenir: local culture as art creation and production idea - Ponimin Ponimin (International Journal of Visual and Performing Arts, 2021)
The tourism industry and craft products are two sectors that are long developed, complementing and strengthening each other. However, not many people consider ceramic craft product design with local culture basis. The research aims to show how local culture can be used as a source for ceramic craft product design ideas. Through design innovation and production techniques, we can increase varieties of ceramic craft product design. However, to make it come true, it needs a creative method as its solution. Creative method application includes: (1) Developing ceramic craft design for souvenir, based on local culture; (2) ceramic craft visual exploration for souvenir sourced from the local culture with Kerapan Sapi Madura (Cow Racing) as creation idea; (3) Ceramic craft production technique for souvenir; (4) Improvement and analysis of ceramic craft product innovation for a souvenir. (5) Analysis of creation result. Creation results can be seen from two design sets of ceramic craft products based on local culture with the “Kerapan Sapi Madura (Cow Racing)” theme as a product design idea.